Blind estimation of reverberation time based on the distribution of signal decay rates - Wen,Y-CJ; Habets,E; Naylor,PA (2008)
The reverberation time is one of the most prominent acoustic characteristics of an enclosure. Its value can be used to predict speech intelligibility, and is used by speech enhancement techniques to suppress reverberation. The reverberation time is u.....